2011
DOI: 10.2319/031811-192.1
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density

Abstract: Objective: To verify whether bone mineral density (BMD) of cortical bone, trabecular bone, and total bone influence the primary stability of orthodontic miniscrews and to verify whether there is a correlation between the measurement of BMD by cone-beam computed tomography (CBCT) and central dual-energy x-ray absorptiometry (DEXA). Materials and Methods: Twenty bovine bone sections were extracted from the pubic and iliac bones from regions with cortical thicknesses of approximately 1 mm. The BMD of the total bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 11 publications
3
25
0
3
Order By: Relevance
“…In a study by Marquezan et al, although no relationship was detected between BMD and cortical bone CT value, a correlation was noted between BMD value and the total bone CT values (38).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Marquezan et al, although no relationship was detected between BMD and cortical bone CT value, a correlation was noted between BMD value and the total bone CT values (38).…”
Section: Discussionmentioning
confidence: 99%
“…12 Several comparative studies confirmed the reliability and high accuracy of 3D CT for quantitative and qualitative analyses [13][14][15] and concluded that CT is a valuable diagnostic supplement to subjective bone density evaluation. [16][17][18] Cone beam computed tomography (CBCT) is preferred in dentistry as a result of the lower radiation dose it affords compared to that required in standard CT. However, standardization between CBCT machines is low, 7 which causes Hounsfield scale variability.…”
Section: Discussionmentioning
confidence: 99%
“…The mini-implants were placed by a single operator with the use of a manual key connected to a digital torque meter (Lutron TQ-8800; Lutron, Taipei, Taiwan). To guarantee perpendicular insertion of the miniscrews into the bone, the torque meter and the bone blocks were adapted to a mechanical device 16 ( Figure 1). The peak insertion torque (IT) values were recorded in Newton centimeters (Ncm).…”
Section: Insertion Torquementioning
confidence: 99%